Avaliação in vivo e in vitro do potencial citotóxico, genotóxico e mutagênico da água e do sedimento do rio Corumbataí - São Paulo, Brasil - Souza, Livia Loureiro [UNESP] (2014)
Aquatic ecosystems are the most affected by pollution from toxic waste emissions of industrial, domestic and agricultural effluents. This contamination may occur in both water and sediments of aquatic environments and induce many adverse effects to the living organisms. The Corumbataí river basin, located within the state of São Paulo (Brazil), has great economic and environmental importance to the state. The waters of this river suffer from various environmental impacts characterized by the disposal of municipal and industrial effluents from cities located close to its border. Thus, this river receives a considerable amount of potentially toxic substances. Due to its importance for public water supply in the region this study aimed to evaluated the cytotoxic, genotoxic and mutagenic effects of water and sediments samples from this water resource, by means of bioassays. For this study, two sampling campaigns were performed, one in the warm and rainy season and the other in the cold and dry season. Samples were collected in Corumbataí River, in four different sites: P1) upstream the municipality of Rio Claro, P2) downstream the municipality of Rio Claro; P3) downstream the confluence of Corumbataí River and Ribeirão Claro; P4) upstream the municipality of Piracicaba. The evaluations were performed through bioassay with the Allium cepa test organisms and culture of hepatocytes from rainbow trout RTL - W1. According to obtained results in this work, it was possible to observed that water and sediments Corumbataí have genotoxic and mutagenic characteristics. The most significant results were recorded for the points P2 and P3, located near the cities of Rio Claro and Santa Gertrudes. Our results also indicated that samples collected at P3 were more affected, probably due to influence of discharges of industrial and domestic effluents from the city of St. Gertrudes , which is considered the largest ceramic hub of America